Analysis of cytokine profiles in aqueous humor based on optical coherence tomography in pachychoroid spectrum diseases - Caiyun Zhang; Yu Zhao; Shian Zhang; Ziyi Xiang; Lijun Shen; Jianbo Mao (Scientific Reports)
Abstract This study investigated cytokine profiles in the aqueous humor (AH) of 172 eyes with central serous chorioretinopathy (CSC, n = 65), pachychoroid neovasculopathy (PNV, n = 24), polypoidal choroidal vasculopathy (PCV, n = 43), and controls (n = 40). AH samples were analyzed using a multiplex bead assay for cytokines including vascular endothelial growth factor (VEGF), interleukin-6 (IL-6), IL-8, IL-10, IP-10, and MCP-1. Results showed no significant differences in IL-6 (P = 0.122) and MCP-1 (P = 0.054) levels among groups. However, VEGF levels were significantly higher in CSC, PNV, and PCV compared to controls (all P < 0.05). In CSC and PNV, only VEGF was elevated without significant changes in other inflammatory cytokines, suggesting that inflammation was not a dominant factor. In contrast, PCV exhibited significantly higher levels of VEGF, IL-10, and IP-10, indicating distinct cytokine profiles. These findings suggest that elevated angiogenic and inflammatory cytokines may contribute to the pathogenesis of PCV.